The provision of care to adults with an intellectual disability in the UK. A Special report from the intellectual disability UK chapter ILAE. (March 2018) - Kerr, M.P.; Watkins, L.V.; Angus-Leppan, H.; Corp, A.; Goodwin, M.; Hanson, C.; Roy, A.; Shankar, R.; ,
Highlights: Care for people with epilepsy and intellectual disability (ID) is 'fragmented'. People with epilepsy and ID often have complex needs and multiple co-morbidities. People with epilepsy and ID wait longer for routine investigations. A minority of clinicians do not consider some non-pharmacological interventions. Recommendations are made to improve care provision for people with epilepsy and ID. Abstract: Purpose: This article reflects the report by the British Branch of the International League Against Epilepsy (ILAE) Working Group on services for adults with epilepsy and intellectual disability (ID). Its terms of reference was to explore the current status of aspects of the care of people with an ID and epilepsy. Methods: Survey content was developed from key themes identified by consensus of the working group. An electronic survey was distributed via email. The sample population was the membership of the ILAE UK, Royal College of Psychiatrists (RCPsych) Faculty of ID, Epilepsy Nurses Association (ESNA), and the Association of British Neurologists (ABN). Following a six week response period the data was then collated, anonymised and distributed to the working group in order that opinion statements could be gathered. Results: The time taken for individuals with both new-onset and established epilepsy to undergo routine investigation was commonly at least 1–3 months, far beyond recommendations made by NICE (CG20). A small minority of clinicians would not consider non-pharmacological interventions including epilepsy surgery, vagus nerve stimulation, and ketogenic diet for this population. Almost universally responders are actively involved in the assessment and management of key risk areas including risk of drowning, hospitalization, medication side effects, and sudden unexpected death in epilepsy (SUDEP). Conclusion: This investigation identifies key themes and recommendations relating to care delivery and meeting the complex needs of people with ID and epilepsy. Adults with ID and epilepsy appear to exist in a unique, but inadequate, segment of epilepsy care delivery.